Eco-friendly microgrid carport charging station for electric vehicles (EVs) - M.M. Jaganath; Saheli Ray; N.B. Dev Choudhury (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
Utilizing renewable energy sources is a crucial and promising way to reduce CO2 emissions and global warming. The use of electric vehicles (EVs) in transportation has signaled a paradigm change from earlier technologies that relied on fossil fuels. This paper provides a techno-economic feasibility study of an optimal energy layout configuration for an EV charging station carport infrastructure. The geographical and meteorological data of the location for the EV charging station carport infrastructure is obtained from NASA through HOMER software. Two different locations are considered as case 1 and case 2. Solar PV/Battery/WT/Converter is the optimum energy arrangement in terms of optimization for case 1, where the net present value of the optimised energy flow is $ 212,096, and the cost of energy (COE) is $ 0.450 per kWh. The best energy configuration in case 2 is solar PV/Battery/Converter, with a COE of $ 0.476 per kWh and a net present value of $ 224,524. The optimal HRES design results in 100% renewable generation, as compared to the study's grid connection scenario, which emits 632 g/kWh of CO2, 2.74 g/kWh of sulfur dioxide, and 1.34 g/kWh of nitrogen oxide into the environment. This study presents the individual degradation cost of the hybrid system components and battery state of charge (SoC), as well as a quick overview of the cyber-security features in EVs. An optimal hybrid microgrid offers both social and environmental benefits to EV owners.